Integrative taxonomy of calcareous sponges (subclass Calcinea) from the Peruvian coast: morphology, molecules, and biogeography - Azevedo, F.; Cóndor-Luján, B.; Willenz, P.; Hajdu, E.; Hooker, Y.; Klautau, M. (Zoological Journal of the Linnean Society, 2015)
Understanding of evolution and systematics of Calcarea (Porifera) have not yet met a corresponding increase in the knowledge of diversity and distribution of these sponges in several parts of the world. Peru is an emblematic example of this lack of taxonomic knowledge, as only three shallow-water species of sponges have hitherto been reported from its 3000 km coast. With the aim of studying sponges of Peru, an integrative taxonomy approach (morphology, molecules, and biogeography) was used in order to achieve sound species identifications. The first findings of calcareous sponges are presented here. Eight species are described in the subclass Calcinea, of which five are new to science. The retrieved biogeographical patterns are either locally endemic, widespread, or discontinuous over large areas. Clathrina antofagastensis was previously known from Chile, while C. aurea and Ernstia tetractina had been reported from the Atlantic (Brazil), and thus represent the first genetically confirmed tropical amphi-American distributions of species not yet found on both sides of the Isthmus of Panama. Our results reveal a richer Tropical East Pacific sponge fauna than the Warm Temperate South-Eastern Pacific one.